Characteristics of Sleep Patterns in Patients Before COVID-19 Diagnosis - Agus Purnama; Irfan Hardian; Dayana Noprida; Hana Febriyanti; Aisah Mamang; Kemala Desi Wahidi; Nurmawati Nurmawati; Lusiana Primasari; Rinawati Rinawati; Sri Murtini; Yusuf Dwiyanto; Muhammad Hadi; Nyimas Heny Purwanti (Universitas STRADA Indonesia, 2021)
Sleep pattern is an important indicator for a person's immunity rather than being susceptible to infection. The purpose of this study was to describe the characteristics of respondents infected with Covid-19 and a history of sleep patterns before being infected. The method in this research is a quantitative description with the PSQI instrument as data collection related to sleep patterns, the sample used is 103 respondents with analysis using SPSS and Rapid Miner. The results showed that most of the respondents were female (56.3%), ages 26-35 (38.9%), higher education level (76.7%), private employees (52.4%), and the quality of sleep bad (53.4%). The conclusion in this study is that good or quality sleep is one of the key factors to maintain the immune system and body metabolism so that it can be immune from several infections that can enter the body, including the Covid-19 pandemic